Genomic analysis of 10 years of artificial selection in community-based breeding programs in two Ethiopian indigenous sheep breeds - Rekik, Emna; Ahbara, Abulgasim; Abate, Zelalem; Goshme, Shenkute; Getachew, Tesfaye; Haile, Aynalem; Rischkowsky, Barbara; Mwacharo, Joram (Wiley, 2022)
In recent times, community-based breeding programs (CBBPs) have been advocated as the best strategy for genetic improvement of local breeds in smallholder farms in developing countries. Since 2009, CBBPs have been implemented for Ethiopian Bonga and Menz sheep to improve growth rates resulting in significant genetic gains in 6-month weights. With the hypothesis that selection could be impacting their genomes, we systematically screened for possible genome changes in the two breeds by analyzing 600K BeadChip genotype data of 151 individuals (with the highest breeding values for 6-month weights) from CBBP f locks against 98 individuals from non-CBBP f locks. We observed no differences in genetic diversity and demographic dynamics between CBBP and non-CBBP f locks. Selection signature analysis employing ROH, logistic regression genome-wide association study, FST, XP-EHH and iHS revealed 5 (Bonga) and 11 (Menz) overlapping regions under selection, that co-localized with QTLs for production (body size/weight, growth, milk yield), meat/milk quality, and health/parasite resistance, suggesting that the decade- long selection has likely started to impact their genomes. However, genome- wide genetic differentiation between the CBBP and non-CBBP f locks is not yet clearly evident.